Cleaning Up After a Hurricane — Safety Comes First! - Astrid Delgado; Eliana Kampf; Carol Lehtola; Traci Partin; Mary Duryea; Edward Gilman (EDIS)
FOR-115, a 3-page full-color fact sheet by Astrid Delgado, Eliana Kampf, Carol Lehtola, Traci Partin, Mary Duryea, and Edward Gilman, is the first chapter in the Urban Forest Hurricane Recovery Program series. It gives tips on chainsaw safety, creating a safe work zone, and personal protective equipment.  Published by the UF School of Forest Resources and Conservation, January 2007.